Chronicle of the 20th century - Dorling kindersley Multimedia (Firm) (New York: DK Multimedia, 1996)
Explore fads and fashions, politicis and personalities, wars and sports, science and cinema of the 20th century.
Title from disc label
System requirements: IBM compatible; multimedia PC, with a 486DX/50 MHz or higher microprocessor; 8MB RAM (12 MB recommended for Windows 95); Windows 3.1 or 95; MPC-compatible double-spreed CD-ROM drive and sound card; mouse; SVGA 256-color display (16 bit colors preferred); loudspeakers or headphones.
System requirements for macintosh (minimum): 68LC040, 25Mhz processor; 12MB RAM, 32 MB hard drive space; System 7.0 or higher; double-speed CD-ROM drive; 640x480 pixel 256-color display (thousands of colors preferred); 8-bit audio; loudspeakers or headphones; mouse
Keywords: History, Modern -- 20th century -- Sources -- Interactive multimedia; Interactive multimedia; CD-ROMs.; Computer software